Recycled polyester fiber and blended interwoven yarn

By processing recycled polyester resin with specific characteristics and filtering to remove contaminants, the challenges of producing high-quality recycled polyester fibers are addressed, achieving comparable mechanical properties and productivity to virgin fibers while promoting environmental sustainability.

JP2025066758AInactive Publication Date: 2025-04-23UNITIKA TRADING CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2025005516
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-23
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for recycling polyester fibers struggle to completely remove non-polyester resin contaminants, leading to poor quality recycled polyester fibers with reduced productivity and mechanical properties.

Method used

The development of recycled polyester fibers made from a recycled polyester resin containing a high ratio of recycled polyester raw materials, processed to achieve specific characteristics such as low diethylene glycol content, controlled carboxyl terminal group concentration, and filtered to minimize foreign matter, allowing for high productivity and excellent mechanical properties.

Benefits of technology

The resulting recycled polyester fibers have improved mechanical properties and productivity, comparable to those made from virgin polyester resin, while also being environmentally friendly due to high recycled content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025066758000001_ABST
    Figure 2025066758000001_ABST
Patent Text Reader

Abstract

To provide ultrafine polyester fibers made of recycled polyester resin containing a high percentage of recycled polyester raw materials derived from used polyester products and unadopted polyester generated in a process of manufacturing polyester products, which can be obtained as productively as when only virgin polyester resin is used and have excellent mechanical properties.SOLUTION: There are provided polyester fibers made of recycled polyester resin containing a component derived from at least one of the following recycled polyester raw materials: a) used polyester products and b) unadopted polyester generated in the process of manufacturing polyester products, and having a single fiber fineness of 0.2 to 0.9 dtex, a filament count of 40 to 320 filaments, a total fiber count of 20 to 200 dtex, and the strength is 1.5 cN / dtex or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a regenerated polyester fiber using a regenerated polyester resin containing a recycled polyester raw material derived from used polyester products and unused polyester generated in the process of manufacturing polyester products, and relates to an ultrafine fiber having a small single fiber fineness and a mixed fiber entangled yarn using the ultrafine fiber. [Background technology]

[0002] Polyethylene terephthalate (PET) has a high melting point, is resistant to chemicals, and is relatively low cost, so it is widely used in fibers, films, and molded products such as PET bottles. These polyester products inevitably generate waste during the manufacturing or processing stages, and are often disposed of after use. However, when incinerated, high heat is generated, which causes significant damage to the incinerator and shortens its lifespan. On the other hand, when not incinerated, the waste remains semi-permanently because it does not decompose.

[0003] In recent years, it has become a problem that plastics are a major cause of marine pollution, with a worldwide movement to reduce the use of plastics and switch to biodegradable plastics. Plastics are a major cause of marine pollution, and in recent years, plastics have been found to be harmful to marine ecosystems. Plastics are a major cause of marine pollution, and in recent years, plastics have been found to be harmful to marine ecosystems. In light of these environmental issues, various methods of recycling are being used to reuse resources. For polyester products such as PET, in addition to recycling polyester waste generated during the manufacturing process, methods are being considered for collecting products that were once on the market and then discarded and reusing them as raw materials. In particular, in recent years, textile products that have been given the Eco Mark, which is certified as having achieved a certain recycling rate, have become widespread.

[0004] Various methods have been proposed for recycling polyester raw materials, such as polyester waste generated in the manufacturing process or recovered used polyester products. For example, there have been proposed a method of adding methanol to PET scraps to decompose them into dimethylene terephthalate (hereinafter sometimes referred to as "DMT") and ethylene glycol (hereinafter sometimes referred to as "EG") (Patent Document 1), a method of adding EG to PET scraps to depolymerize them, and then adding methanol to recover DMT (Patent Document 2), and a method of depolymerizing PET scraps with EG to form oligomers, which are then used in a polycondensation reaction (Patent Document 3).

[0005] Incidentally, impurities that can become a problem when recycling PET bottles and other products that have already been made include various additives added to the polyester resin, as well as items attached to the bottle itself, such as a) caps (aluminum, polypropylene, polyethylene), b) inner stoppers, c) liners (polypropylene, polyethylene), d) labels (paper, resins such as polystyrene, ink), e) adhesives, and f) printing ink. Generally, as a pretreatment step for the recycling process, the collected PET bottles are put through a vibrating sieve to remove sand, metal, etc. The PET bottles are then washed, and the colored bottles are separated before being roughly crushed. Labels, etc. are then removed by wind separation. Furthermore, aluminum pieces from the caps, etc. are removed and the PET bottle pieces are finely crushed. Components such as adhesives, proteins, and mold are removed by high-temperature alkaline washing, and different components such as polypropylene and polyethylene are separated by differences in specific gravity.

[0006] However, even after going through these steps, it is difficult to completely separate and remove non-polyester resins, particularly polypropylene, polyethylene, polystyrene, etc., from PET resin. For example, even if the production of recycled polyester resin is attempted by the recycling methods described in Patent Documents 1 to 4, the removal of foreign matter derived from non-polyester resins cannot be sufficiently performed, and the amount of foreign matter mixed in cannot be sufficiently reduced, making it difficult to obtain a product with the same quality as virgin polyester resin. If the amount of foreign matter mixed in is not sufficiently reduced in this way, the pressure rise rate of the filtration filter in the spinning process or film-forming process is fast, long-term continuous operation is not possible, and processing operability becomes very poor. Moreover, the methods described in Patent Documents 1 to 3 require a large amount of cost for the installation, operation, maintenance, etc. of the recovery device, and there is room for improvement in terms of practicality.

[0007] The invention described in Patent Document 4 describes a method in which polyester waste is depolymerized with ethylene glycol, filtered through a filter with an average mesh size of 10 to 50 μm, and then repolymerized. It is also shown that the obtained recycled polyester resin has a low amount of foreign matter mixed in and is excellent in operability during processing. However, even with this method, the above-mentioned foreign matter derived from the non-polyester resin cannot be sufficiently removed, and the amount of the foreign matter mixed in cannot be sufficiently reduced. As described above, a recycled polyester resin that can sufficiently remove not only various inorganic substances but also foreign matter derived from non-polyester resins, and that can produce various products similar to those produced from virgin polyester resins and that can produce high-quality products has not yet been obtained.

[0008] In particular, when polyester resin is used for melt spinning to obtain fibers, the amount of foreign matter mixed in has a significant effect on productivity. The more complex the shape of the fiber is or the finer the fiber is, the more the foreign matter affects it, making production difficult and resulting in poor mechanical properties of the obtained fiber. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Special Publication No. 42-8855 [Patent Document 2] Japanese Patent Publication No. 48-62732 [Patent Document 3] Japanese Patent Application Laid-Open No. 60-248646 [Patent Document 4] JP 2005-171138 A Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention aims to solve the above problems and provide an ultrafine polyester fiber made of recycled polyester resin containing a high proportion of recycled polyester raw material derived from used polyester products and unused polyester generated in the process of manufacturing polyester products, which can be obtained with the same productivity as when only virgin polyester resin is used, and which has excellent mechanical properties. [Means for solving the problem]

[0011] The present inventors conducted extensive research to solve the above problems and arrived at the present invention. That is, the present invention relates to the following (1) to (6). (1) A polyester fiber made of a recycled polyester resin containing a component derived from at least one type of recycled polyester raw material, i.e., a) used polyester product and b) unused polyester generated in the process of manufacturing the polyester product, the recycled polyester fiber having a single fiber fineness of 0.2 to 0.9 dtex, a filament count of 40 to 320, a total fineness of 20 to 200 dtex, and a strength of 1.5 cN / dtex or more. (2) The recycled polyester fiber according to (1), wherein the recycled polyester resin has a diethylene glycol content of 4 mol% or less and a carboxyl end group concentration of 30 equivalents / t or less, when the total amount of all glycol components is taken as 100 mol%. (3) A mixed entangled yarn which is composed of the recycled polyester fiber according to (1) or (2) and a polyester fiber having a single fiber fineness of 1.0 to 5.0 dtex and has a total fineness in the range of 40 to 300 dtex, the mixed entangled yarn having a false twist crimp as a whole, and having protrusions formed of the recycled polyester fibers on the surface of the mixed entangled yarn. (4) The mixed fiber entangled yarn according to (3), wherein the polyester fiber having a single fiber fineness of 1.0 to 5.0 dtex is a polyester fiber made of a recycled polyester resin containing a component derived from at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in the process of manufacturing a polyester product. (5) Woven or knitted fabrics containing the recycled polyester fibers described in (1) or (2). (6) A woven or knitted fabric containing the mixed fiber intertwined yarn according to (3) or (4). Effect of the Invention

[0012] The regenerated polyester fiber of the present invention is a fiber made of a regenerated polyester resin containing a small amount of foreign matter, and has a carboxyl end group concentration and a diethylene glycol content that satisfy specific ranges, so that even ultrafine fibers with small single fiber fineness can be produced in a process of obtaining fibers by melt spinning over a long period of time, and can be produced with good productivity. Therefore, the regenerated polyester fiber of the present invention has mechanical property values ​​similar to those of fibers using virgin polyester resin, and can be used alone to obtain products such as woven and knitted fabrics, and can also be combined with other fibers to obtain various processed yarns. The mixed fiber entangled yarn of the present invention uses ultrafine fibers made of recycled polyester resin as its constituent fibers, and therefore has the same properties as when ultrafine fibers made of virgin polyester resin are used, making it possible to use it for various purposes and to make it environmentally friendly. [Brief description of the drawings]

[0013] [Figure 1]FIG. 2 is a schematic diagram for explaining an example of a method for producing a mixed and entangled yarn of the present invention. [Diagram 2] FIG. 2 is a schematic diagram for explaining another example of the method for producing a mixed and entangled yarn of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below. The recycled polyester fiber of the present invention is made of a) used polyester products and b) recycled polyester resin containing a component derived from at least one recycled polyester raw material, i.e., polyester scraps generated in the process of producing polyester resin or polyester products.

[0015] The recycled polyester resin constituting the recycled polyester fiber of the present invention (hereinafter, sometimes referred to as the "resin of the present invention") contains a component derived from at least one type of recycled polyester raw material, i.e., a) used polyester products and b) unused polyester generated in the process of manufacturing polyester products. Examples of used polyester products in the above category a) include polyester molded products (including fibers) that were once on the market and then collected after use, etc. Representative examples of such products include containers such as PET bottles and packaging materials.

[0016] The unadopted polyester generated in the manufacturing process of polyester products mentioned in b) above is polyester that has not been commercialized. Examples of such unadopted polyester include off-standard resin pellets, materials that are no longer needed during molding, pieces cut during molding, scraps generated during molding or processing, cut-up pieces of transitional products generated when changing brands, and cut-up pieces of prototypes or defective products. The above a) and b) are not limited in terms of their form, and may be pelletized by further processing such as crushing and cutting as necessary, or may be melted and pelletized.

[0017] The recycled polyester raw materials a) and b) above may be either crystalline or amorphous. Therefore, for example, pellets of amorphous polyester waste that have not been heat-treated, crystalline pellets that have been heat-treated, or a mixture of crystalline pellets and amorphous pellets can be used. In the present invention, it is preferable to use crystalline recycled polyester raw materials, particularly for the purpose of preventing fusion between pellets during charging into the can or depolymerization reaction. Therefore, the materials a) or b) above that have been crystallized by heat treatment (crystallized pellets, etc.) can be suitably used.

[0018] The resin of the present invention preferably contains 40% by mass or more of the recycled polyester raw material, and more preferably 50% by mass or more. If the content of the recycled polyester raw material is less than 40% by mass, the purpose of considering environmental issues cannot be achieved. There is no particular upper limit to the content of the recycled polyester raw material, but according to the manufacturing method of the recycled polyester resin described later, it is possible to easily obtain a recycled polyester resin with a content of the recycled polyester raw material of 40 to 80% by mass.

[0019] The resin of the present invention satisfies the following characteristic values ​​(1) and (2) at the same time, and preferably satisfies characteristic value (3). In other words, by employing the production method described below, the resin of the present invention can satisfy these characteristic values, and has properties equivalent to those of virgin polyester resin. (1) When the total amount of all glycol components is 100 mol %, the diethylene glycol content is 4 mol % or less. (2) The carboxyl end group concentration is 30 equivalents / t or less. (3) The average pressure rise rate is 0.6 MPa / h or less. However, the average pressure rise rate is a value calculated by the following procedure. Using a pressure rise tester including an extruder and a pressure sensor, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm) is set at the tip of the extruder, polyester resin is melted at 300° C. in the extruder, and the melt is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)" and the pressure value at the time of continuous extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)." Based on these pressure values, the average pressure rise rate is calculated by the following calculation formula A. Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A)

[0020] In the resin of the present invention, when the total amount of all glycol components is 100 mol%, the diethylene glycol content is 4 mol% or less, and preferably 3.5 mol% or less. In particular, in the resin of the present invention obtained by the production method described below, ethylene glycol is used as one of the raw materials, and diethylene glycol may be generated as a by-product. The resin of the present invention has a small amount of diethylene glycol as a by-product, and has excellent crystallinity due to the diethylene glycol content being 4 mol% or less. Therefore, melt spinning can be performed with good productivity like virgin polyester, and it is possible to obtain fibers with excellent mechanical properties such as strength and elongation. The lower limit of the diethylene glycol content can be, for example, about 0.5 mol%, but is not limited thereto.

[0021] The resin of the present invention has a carboxyl end group concentration of 30 equivalents / t or less, preferably 25 equivalents / t or less, and most preferably 20 equivalents / t or less. By making the carboxyl end group concentration 30 equivalents / t or less, the resin has excellent heat resistance, can be melt spun with good productivity like virgin polyester, and can obtain fibers with excellent mechanical properties such as strength and elongation. The lower limit of the carboxyl end group concentration can be, for example, about 5 equivalents / t, but is not limited thereto.

[0022] The resin of the present invention preferably has an average pressure rise rate of 0.6 MPa / h or less, more preferably 0.5 MPa / h or less, and even more preferably 0.4 MPa / h or less, as measured by the following method. The average pressure rise rate in the present invention is an index of the amount of foreign matter derived from various inorganic substances or foreign matter derived from non-polyester resins, and the smaller the average pressure rise rate, the smaller the amount of foreign matter. By having an average pressure rise rate of 0.6 MPa / h or less, melt spinning can be performed with good productivity like virgin polyester, and it is also possible to produce fibers with excellent mechanical properties such as strength and elongation. The lower limit of the average pressure rise rate can be, for example, about 0.01 MPa / h, but is not limited thereto.

[0023] The average pressure rise rate was measured using a pressure rise tester including an extruder and a pressure sensor. A stainless steel twill weave filter with a filtration grain size of 12 μm was attached to the tip of the extruder. The polyester resin was melted in the extruder at 300° C., and the melt was extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion was taken as the "initial pressure value (MPa)" and the pressure value at the point when extrusion was continued for 12 hours was taken as the "final pressure value (MPa)." The average pressure rise rate was calculated based on these pressure values ​​using the following formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A) This is the method used.

[0024] The resin of the present invention is not particularly limited in type, but is preferably composed mainly of polyethylene terephthalate (PET). The content of PET in the polyester resin of the present invention is preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90 to 100% by mass. Therefore, for example, recycled polyester resins with a PET content of 95 to 99% by mass are also included in the present invention.

[0025] In particular, in the manufacturing method of the resin of the present invention described later, PET, which is usually a polycondensation product of ethylene glycol and terephthalic acid, can be obtained, but when components other than ethylene glycol and terephthalic acid are present in the recycled polyester raw material, polyester resins other than PET may be produced by the polycondensation reaction. Therefore, the resin of the present invention may contain, in addition to the main component PET, the following components as acid components or glycol components copolymerized therein. Two or more of these components may be included.

[0026] Examples of the acid component include isophthalic acid, phthalic acid, phthalic anhydride, naphthalenedicarboxylic acid, adipic acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, dodecanedioic acid, dimer acid, and further trimellitic anhydride, trimellitic acid, pyromellitic acid, 1,4-cyclohexanedicarboxylic acid, sebacic acid, dimer acid, etc. Examples of the glycol component include neopentyl glycol, 1,4-butanediol, 1,2-propylene glycol, 1,5-pentanediol, 1,3-propanediol, 1,6-hexamethylenediol, diethylene glycol, 1,4-cyclohexanedimethanol, dimer diol, butylethylpropanediol, (2-methyl-1,3-propanediol, trimethylolpropane, glycerin, pentaerythritol, ethylene oxide adducts of bisphenol A or bisphenol S, etc.

[0027] The regenerated polyester fiber of the present invention is a multifilament fiber having a single fiber fineness of 0.2 to 0.9 dtex, a filament count of 40 to 320, and a total fineness of 20 to 200 dtex. Among these, the single fiber fineness is preferably 0.6 dtex or less, and particularly preferably 0.2 to 0.6 dtex. The number of filaments is preferably 50 to 300, and particularly preferably 50 to 180. The total fineness is preferably 30 to 150 dtex, and particularly preferably 40 to 120 dtex.

[0028] The regenerated polyester fiber of the present invention uses the resin of the present invention having the above-mentioned characteristic values, and therefore has little foreign matter and excellent heat resistance (thermal stability), so that it is possible to obtain a polyester fiber having a small single fiber fineness similar to that obtained when a virgin polyester resin is used. Furthermore, by using the resin of the present invention, the regenerated polyester fiber of the present invention can have a strength of 1.5 cN / dtex or more and an elongation of 10 to 300% even though the single fiber fineness is small. The regenerated polyester fiber of the present invention may be either a drawn yarn or an undrawn yarn, and in the case of a drawn yarn, it is preferable that the strength is 2 cN / dtex or more and the elongation is 20 to 60%, and in the case of an undrawn yarn, it is preferable that the strength is 1.5 cN / dtex or more and the elongation is 50 to 200%.

[0029] Next, the mixed and entangled yarn of the present invention will be described. The mixed and entangled yarn of the present invention is composed of the regenerated polyester fiber of the present invention (hereinafter, sometimes referred to as regenerated polyester fiber (A)) and polyester fiber (B) having a single fiber fineness of 1.0 to 5.0 dtex, and has a total fineness in the range of 40 to 300 dtex, more preferably 50 to 180 dtex.

[0030] In the mixed entangled yarn of the present invention, the single fiber fineness of the regenerated polyester fiber (A) and the polyester fiber (B) are set within the specific ranges as described above, so that the regenerated polyester fiber (A) and the polyester fiber (B) can be sufficiently entangled. This entanglement makes it easy to form protrusions due to the relatively thin regenerated polyester fiber (A) on the surface of the mixed entangled yarn of the present invention. In the present invention, the protrusions due to the regenerated polyester fiber (A) refer to the parts of the surface of the mixed entangled yarn where the regenerated polyester fiber (A) protrudes outward due to loops, slack, etc. of the regenerated polyester fiber (A).

[0031] The polyester fiber (B) has a single fiber fineness of 1.0 to 5.0 dtex, preferably 1.5 to 3.0 dtex. The total fineness is preferably 20 to 70 dtex, preferably 20 to 50 dtex. If the single fiber fineness is less than 1.0 dtex, it becomes difficult to maintain the fine protrusions formed by the regenerated polyester fiber (A) on the surface of the mixed fiber entangled yarn. If the single fiber finenesses of the regenerated polyester fiber (A) and the polyester fiber (B) are approximately the same, when the mixed fiber entangled yarn is made into a woven or knitted fabric, the woven or knitted fabric becomes too soft and tends to lack tension and stiffness.

[0032] On the other hand, if the monofilament fineness of the polyester fiber (B) exceeds 5.0 dtex, the texture of the woven or knitted fabric as a whole will be hard even when it is mixed with the regenerated polyester fiber (A) having a monofilament fineness in the above range. Furthermore, the intertwining state will be deteriorated, making it difficult to form the above-mentioned fine protrusions on the surface of the woven or knitted fabric. If the total fineness of the polyester fiber (B) is less than 20 dtex, there is a problem that it is difficult to retain the fine protrusions formed by the regenerated polyester fiber (A) on the surface part of the mixed intertwined yarn, while if it exceeds 70 dtex, there is a problem that the texture of the woven or knitted fabric as a whole will be hard even when it is mixed with the regenerated polyester fiber (A).

[0033] The polyester fiber (B) is preferably made of a polyester resin mainly composed of PET, but considering environmental issues, it is preferably made of a recycled polyester resin containing a component derived from at least one recycled polyester raw material, i.e., a) used polyester products and b) unused polyester generated in the process of manufacturing polyester products. Among them, the recycled polyester resin is preferably the resin of the present invention.

[0034] The mixed fiber entangled yarn of the present invention has a false twist crimp as a whole. In the mixed fiber entangled yarn of the present invention, the degree of false twist crimp, i.e., the crimp rate, is preferably 10 to 45%, more preferably 20 to 40%. Since the mixed fiber entangled yarn has an appropriate crimp rate, it becomes easy to form the above-mentioned fine protrusions on the surface of the mixed fiber entangled yarn. When the crimp rate of the mixed fiber entangled yarn is less than 10%, it is difficult to form the above-mentioned protrusions on the surface of the mixed fiber entangled yarn due to the low crimp rate, and the water repellency cannot be fully exhibited when the mixed fiber entangled yarn is made into a woven or knitted fabric. When the crimp rate of the mixed fiber entangled yarn exceeds 45%, the stretchability of the mixed fiber entangled yarn is too strong, so it is not suitable for a highly water-repellent woven or knitted fabric. That is, when the mixed fiber entangled yarn is stretched, it becomes a flat structure, so it becomes difficult to maintain the above-mentioned protrusions, and the water repellency decreases.

[0035] In the present invention, the crimp rate of the mixed fiber entangled yarn is a value obtained by measuring it by the following method. First, the mixed fiber entangled yarn is wound 5 times using a measuring machine with a frame circumference of 1.125 m, and then the skein is hung on a stand in a free state at room temperature for a day and a night. Next, the skein is put into boiling water while applying a load of 0.000147 cN / dtex, and is subjected to a wet heat treatment for 30 minutes. Then, the skein is taken out, the moisture is lightly removed with filter paper, and it is left in a free state at room temperature for 30 minutes. Then, a load of 0.000147 cN / dtex and 0.00177 cN / dtex (light load) are applied to the skein, and the length X is measured. Next, while still applying the load of 0.000147 cN / dtex, a load of 0.044 cN / dtex (heavy load) is applied instead of the light load, and the length Y is measured. Then, it is calculated based on the formula: crimp rate (%) = (YX) / Y x 100. The crimp rate is measured for five pieces of the mixed fiber entangled yarn, and the average value (n = 5) is regarded as the crimp rate of the yarn.

[0036] In the mixed fiber entangled yarn of the present invention, the mass ratio (A / B) of the recycled polyester fiber (A) to the polyester fiber (B) is preferably in the range of 45 / 55 to 80 / 20, and more preferably in the range of 50 / 50 to 75 / 25. If the mass ratio (mixing ratio) of the recycled polyester fiber (A) is less than 45%, it becomes difficult to form the above-mentioned protrusions on the surface of the mixed fiber entangled yarn, and it becomes difficult to impart sufficient water repellency to the woven or knitted fabric. In addition, the proportion of recycled polyester resin used in the mixed fiber entangled yarn becomes small, making it impossible to make the fiber environmentally friendly. On the other hand, if the blend ratio of the recycled polyester fiber (A) exceeds 80%, the ratio of the polyester fiber B is too small, making it difficult to maintain the above-mentioned protrusions on the surface. As a result, the fine protrusions are easily crushed, making it difficult to impart sufficient water repellency to the woven or knitted fabric.

[0037] The mixed fiber entangled yarn of the present invention is mixed and entangled as a whole yarn. The number of entanglements of the mixed fiber entangled yarn is preferably 150 to 200 / m, more preferably 160 to 190 / m. If the number of entanglements is less than 150 / m, the entangled state may be easily undone, and it may be difficult to form the above-mentioned fine protrusions on the surface of the mixed fiber entangled yarn. In addition, if the entangled state is easily undone, a guide wear inevitably received in the manufacturing process of the woven or knitted fabric may cause a shift in the yarn, which may easily induce defects in the woven or knitted fabric. On the other hand, if the number of entanglements exceeds 200 / m, the regenerated polyester fiber (A) and the polyester fiber (B) are too entangled, the crimp disappears, and the above-mentioned protrusions are hardly formed, so that it becomes difficult to impart sufficient water repellency to the woven or knitted fabric. In the present invention, the number of entanglements of the mixed fiber entangled yarn is a value obtained by measurement based on the JIS L1013 8.15 hook method.

[0038] The mixed fiber entangled yarn of the present invention uses the recycled polyester fiber of the present invention, and therefore can have the same strength and elongation as when virgin polyester resin is used. The strength is preferably 2.5 cN / dtex or more, and the elongation is preferably 20 to 60%.

[0039] Next, a method for producing the resin of the present invention will be described. In the method for producing the resin of the present invention, it is important to carry out the steps (1) to (5) in this order. (1) Add a slurry of ethylene glycol and terephthalic acid to obtain ethylene terephthalate oligomers. (2) Ethylene glycol is added to the oligomer obtained in (1). (3) The recycled polyester raw material is added to the oligomer obtained in (2) to which ethylene glycol has been added under normal pressure while stirring so that the molar ratio of total glycol components / total acid components becomes 1.08 to 1.35, and depolymerization is performed under heat treatment conditions of 245 to 280°C. (4) The depolymerized polymer obtained in (3) is passed through a metal filter having a filtration grain size of 10 to 25 μm to filter out foreign matter. (5) A polymerization catalyst is added to the depolymerized product obtained in (4) after filtering out foreign matter, and a polycondensation reaction is carried out at a temperature of 260° C. or higher and under reduced pressure of 1.0 hPa or less.

[0040] First, in the step (1), a slurry of ethylene glycol and terephthalic acid is added as a preliminary step to depolymerize the recycled polyester raw material [a) used polyester products and b) at least one of unused polyesters generated in the process of manufacturing polyester products] to obtain an esterification reaction product (ethylene terephthalate oligomer). The amount of ethylene terephthalate oligomer is preferably 0.20 to 0.80 mass% and more preferably 0.30 to 0.70 mass% in 100 mass% of the finally obtained recycled polyester resin.

[0041] If the amount of ethylene terephthalate oligomer is less than the above amount, the recycled polyester raw material is likely to block with itself when the recycled polyester raw material is added in step (3), which is undesirable because it places an excessive load on the mixer. On the other hand, if the amount of ethylene terephthalate oligomer is more than the above range, no particular problem occurs in the depolymerization reaction, but the recycling rate of the finally obtained recycled polyester resin is undesirably low.

[0042] In the step (2), ethylene glycol is added to the ethylene terephthalate oligomer obtained in the step (1). In order to sufficiently advance the depolymerization reaction in the step (3), the amount of ethylene glycol added is preferably 5 to 15 mass% relative to 100 mass% of the ethylene terephthalate oligomer, and more preferably 10 to 15 mass%. If the amount of ethylene glycol added exceeds 15 mass%, the ethylene terephthalate oligomer tends to solidify in the reactor, which may make it impossible to continue the subsequent reaction, and this is not preferable. When ethylene glycol is added to the ethylene terephthalate oligomer, it is preferable to uniformize the temperature of the contents while rotating the stirrer before adding the ethylene glycol, in order to prevent the oligomer from solidifying.

[0043] In the step (3), the recycled polyester raw material is added to the oligomer obtained in the step (2) to which ethylene glycol has been added while stirring, so that the molar ratio of total glycol components / total acid components is 1.08 to 1.35, and depolymerization is carried out under heat treatment conditions of 245 to 280°C. In the manufacturing method of the present invention, this step is important. That is, in the conventional method using recycled polyester raw materials, depolymerization is performed using only recycled polyester raw materials, but in the present invention, depolymerization of recycled polyester raw materials is performed in the presence of ethylene terephthalate oligomer and ethylene glycol, and the recycled polyester raw materials are charged with all components of oligomer, ethylene glycol, and recycled polyester raw materials so that the molar ratio of total glycol components / total acid components is 1.08 to 1.35, and depolymerization is performed. The molar ratio of total glycol components / total acid components is preferably 1.10 to 1.33, more preferably 1.12 to 1.30.

[0044] By carrying out the above-mentioned steps (1) to (3), not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that these foreign substances can be filtered out without fail in the step (4).In addition, in the polycondensation reaction in the step (5), it becomes possible to obtain a recycled polyester resin having a diethylene glycol content and a carboxyl end group concentration that are not more than a specific amount as characteristic values ​​of the present invention, and having a small amount of foreign substances mixed in. It is preferable that the above depolymerization reaction does not decompose the recycled polyester raw material into monomers, but into oligomers having a repeating unit of about 5 to 20. By controlling in this way, not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that more foreign substances can be removed.

[0045] If the molar ratio of total glycol components / total acid components during the depolymerization reaction is outside the above range, the resulting recycled polyester resin will not satisfy at least one of the carboxyl end group concentration and diethylene glycol content specified in the present invention, and will have a high average pressure rise rate. This is because, when the molar ratio of total glycol components / total acid components during the depolymerization reaction is outside the above range, the precipitation of various inorganic substances and foreign substances derived from non-polyester resins is not efficiently carried out, and these foreign substances cannot be filtered out completely in step (4), and the foreign substances precipitate after the polycondensation reaction in step (5), resulting in a recycled polyester resin with a high average pressure rise rate.

[0046] The reactor used in the production method of the present invention may be a commonly used esterification reactor without any particular problem in terms of volume and shape of the stirring blades. However, in order to efficiently advance the depolymerization reaction, it is preferable that the reactor has a structure equipped with a distillation column that does not distill ethylene glycol outside the system. When the recycled polyester raw material is charged, it is preferable to do so while stirring under normal pressure, and it is more preferable to charge it in a state where it is purged with a small amount of inert gas (generally nitrogen gas is used).

[0047] The reaction temperature during depolymerization in the step (3) is preferably set at an internal temperature of the reactor in the range of 245 to 280°C, and more preferably set at an internal temperature in the range of 255 to 280°C. If the reaction temperature during depolymerization is less than 245°C, the reaction product solidifies, the operability deteriorates, and even if a recycled polyester resin is obtained, the diethylene glycol content and the carboxyl end group concentration become too high. If the reaction temperature exceeds 280°C, the diethylene glycol content and the carboxyl end group concentration of the obtained recycled polyester resin become too high. In addition, the depolymerization reaction time (the reaction time from the end of the addition of the recycled polyester raw material) is preferably within 4 hours, and more preferably within 2 hours from the viewpoints of suppressing the amount of diethylene glycol as a by-product and suppressing deterioration of the color tone of the polyester.

[0048] In the step (4), the depolymerized product obtained in the step (3) is passed through a metal filter having a filtration size of 10 to 25 μm to filter out foreign matter. As described above, by carrying out the depolymerization reaction under the conditions of the step (3), not only various inorganic substances but also foreign matter derived from non-polyester resins is efficiently precipitated, and therefore, by passing the depolymerized product through a metal filter having a filtration size of 10 to 25 μm, the precipitated foreign matter can be filtered out to obtain a depolymerized product with a small amount of foreign matter.

[0049] If a metal filter with a filtering particle size of more than 25 μm is used, foreign matter in the polymer cannot be sufficiently removed, and the resulting recycled polyester resin contains a large amount of foreign matter. Therefore, when such a resin is used for spinning, the nozzle pack pressure increases and thread breakage occurs. On the other hand, if a metal filter with a filtering particle size of less than 10 μm is used, clogging due to foreign matter easily occurs, and the filter life is shortened, which is disadvantageous in terms of cost and also deteriorates operability.

[0050] As the metal filter that can be used in step (4) of the present invention, any ordinary filter can be used without any particular problems, and examples thereof include a screen changer type filter, a leaf disk filter, and a candle type sintered filter.

[0051] In the manufacturing method of the present invention, a polymerization catalyst is added to the depolymerized product obtained after filtering foreign matter through the above step (4), and a polycondensation reaction is carried out at a temperature of 260°C or higher and a reduced pressure of 1.0 hPa or lower. As the polymerization catalyst, for example, one or more of germanium, antimony, titanium and cobalt compounds can be used, but a germanium or antimony compound is preferably used. Furthermore, when the transparency of the resulting recycled polyester resin is important, it is preferable to use a germanium compound. Examples of germanium or antimony compounds include oxides, inorganic acid salts, organic acid salts, halides, and sulfides thereof. These polycondensation catalysts are used in an amount of 5 x 10 per mole of the acid component of the polyester resin to be produced.-5 It is preferable to set the concentration to 6×10 moles / unit or more. -5 It is more preferable that the amount is mol / unit or more. In addition, since the polymerization catalyst contained in the recycled polyester raw material may also act as a catalyst during the polycondensation reaction, it is preferable to take into consideration the amount and type of polymerization catalyst contained in the recycled polyester raw material when adding the polymerization catalyst in step (4).

[0052] During the polycondensation reaction, a fatty acid ester, a hindered phenol-based antioxidant, or a phosphorus compound may be added in addition to the above-mentioned polymerization catalyst. Specific examples of fatty acid esters include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, dipentaerythritol hexastearate, etc. Among these, glycerin monostearate, pentaerythritol tetrastearate, and dipentaerythritol hexastearate are preferred.

[0053] Hindered phenol antioxidants include 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 4,4'-butylidenebis-(3-methyl-6-t-butylphenol), triethyl Examples of suitable compounds include ethylene glycol-bis[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate] and 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1'-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, but from the standpoint of effectiveness and cost, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane is preferred.

[0054] Examples of phosphorus compounds that can be used include phosphorous acid, phosphoric acid, trimethyl phosphite, triphenyl phosphite, tridecyl phosphite, trimethyl phosphate, tridecyl phosphate, and triphenyl phosphate.

[0055] Then, in the polycondensation reaction tank, the polycondensation reaction is carried out at a temperature of 260° C. or higher and under reduced pressure of 1.0 hPa or lower. If the polycondensation reaction temperature is lower than 260° C. or the pressure during the polycondensation reaction exceeds 1.0 hPa, the polycondensation reaction time becomes long, resulting in poor productivity. The polycondensation reaction temperature is more preferably 270° C. or higher. However, if the polycondensation reaction temperature is too high, the polymer is colored due to thermal decomposition, the color tone is deteriorated, and the amount of terminal groups (COOH) is also increased due to thermal decomposition. Therefore, in the present invention, the upper limit of the polycondensation reaction temperature is preferably 285° C. or lower.

[0056] The intrinsic viscosity of the resin of the present invention obtained by the above polycondensation reaction is preferably 0.5 to 1.0, taking into consideration melt spinning.

[0057] Next, the production methods of the regenerated polyester fiber, the mixed fiber intertwined yarn, and the woven or knitted fabric of the present invention will be described. First, the recycled polyester fiber of the present invention is produced by melting the resin of the present invention at a temperature range of 280 to 310°C using an extruder-type melt spinning machine, spinning it from a spinning nozzle, and winding it up at a spinning speed of 500 to 4000 m / min. The undrawn yarn obtained is drawn in a drawing device at a drawing temperature of 20 to 200°C and a draw ratio of 1.1 to 5.0, and then winding it up (in the case of drawn yarn). In addition, when the recycled polyester fiber of the present invention is not stretched, the resin of the present invention is melted in the temperature range of 280 to 310°C, spun from a spinning nozzle, and wound up at a spinning speed of 4000 to 8000 m / min to obtain the fiber (in the case of unstretched yarn). Furthermore, the fibers may be wound without being stretched as described above and then false-twisted at a processing speed of 100 to 700 m / min and a stretch ratio of 1.10 to 1.30 (in the case of false-twist textured yarn).

[0058] Next, when producing the mixed and entangled yarn of the present invention, the regenerated polyester fiber (A) and the polyester fiber (B) obtained as described above are prepared. It is preferable to use undrawn fibers for both fibers and to apply drawing at the stage of mixed and entangled fibers. The method for producing the mixed fiber entangled yarn of the present invention will be described in detail with reference to the schematic diagram of FIG. 1. First, the packages YA and YB of the recycled polyester fiber (A) and polyester fiber (B) are respectively loaded on a creel. Next, the polyester fiber (B) is introduced to the first supply roller 1. Then, a drawing process is performed in which the polyester fiber (B) is drawn at a draw ratio of 1.1 to 1.4 times between the first supply roller 1 and the second supply roller 2. Here, the draw ratio in the drawing process refers to the ratio between the surface speed of the first supply roller 1 and the surface speed of the second supply roller 2 (draw ratio = surface speed of the second supply roller 2 / surface speed of the first supply roller 1). The higher the elongation, the longer the yarn length becomes in the subsequent composite false twisting process, and the later fiber with the longer yarn length is more likely to be arranged on the outside (surface side) of the mixed fiber entangled yarn. As a result, as described above, it is easier to form a protrusion by the recycled polyester fiber (A) on the surface of the mixed fiber entangled yarn. The protrusions protrude from the portions where the regenerated polyester fibers (A) are loosely entangled and formed on the surface portion of the mixed intertwined yarn.

[0059] The polyester fiber (B) may be stretched at room temperature. Alternatively, as shown in FIG. 2, a second heater 10 or the like may be installed between the first supply roller 1 and the second supply roller 2 to apply heat. This stabilizes the physical properties of the polyester fiber (B), reduces the dyeing difference (color difference) between the recycled polyester fiber (A) and the polyester fiber (B) when dyed, and prevents unevenness when made into a woven or knitted fabric. The hot stretching temperature by the second heater 10 is, for example, about 150 to 190°C.

[0060] Next, a composite false twisting process is carried out in which the stretched recycled polyester fibers (A) and polyester fibers (B) are composite false twisted under predetermined conditions. The composite false twisting is carried out under conditions of a processing speed of 100 to 700 m / min and a draw ratio of 1.10 to 1.30. Specifically, as shown in Fig. 1, the two types of fibers stretched above are simultaneously introduced into the second supply roller 2, passed through the first heater 3 and false twisting tool 4, and pulled out from the first take-up roller 5 to obtain a composite false twisted yarn (C).

[0061] In the composite false-twisted yarn (C), the yarn length of the recycled polyester fiber (A) is preferably about 5% or less longer than the yarn length of the polyester fiber (B), and more preferably about 1 to 4% longer. If the recycled polyester fiber (A) is longer than the polyester fiber (B) by more than 5%, the bulkiness of the composite false-twisted yarn increases, and the protrusions become larger, which reduces the water repellency, which is not preferable.

[0062] In the composite false twisting step, it is preferable to compositely false twist both fibers with an appropriate false twisting tool at a predetermined processing speed and a predetermined draw ratio. False twisting methods are generally broadly classified into a spindle method and a friction method. Either of these methods can be adopted in the present invention.

[0063] After the composite false twisting step, the composite false twisted yarn (C) is guided by the first take-up roller 5 to the fluid nozzle 6, where it is mixed and entangled using the fluid nozzle 6. That is, the composite false twisted yarn obtained in the composite false twisting step is mixed and entangled using a fluid nozzle, for example, under conditions of an air pressure of 0.1 to 0.6 MPa and an overfeed rate of 4 to 5%. There are no particular limitations on the fluid nozzle, but an interlace nozzle is generally preferred.

[0064] The mixed entangled yarn passes through a second take-up roller 7, and is then wound into a package 9 by a winding roller 8. In the mixed entangled yarn of the present invention, if the number of entanglements is in the range of about 150 to 200 pcs / m, it can be said to have appropriate mixed entanglement.

[0065] Next, the woven or knitted fabric of the present invention will be described. [Woven and knitted fabrics 1] The woven or knitted fabric of the present invention (hereinafter referred to as woven or knitted fabric 1) is a woven or knitted fabric containing at least a part of the above-mentioned recycled polyester fiber of the present invention. The content of the recycled polyester fiber of the present invention in the woven or knitted fabric 1 is preferably 80% by mass or more, and more preferably 85% by mass or more. As a result, the obtained woven or knitted fabric 1 has ultrafine polyester fibers arranged at a high density, and can have a soft texture and water repellency. In particular, the woven fabric has excellent waterproofness and water repellency even though it is non-coated. Furthermore, since the content of the recycled polyester fiber of the present invention is 80% by mass or more, it is possible to obtain a woven or knitted fabric that is considerate of the global environment.

[0066] The regenerated polyester fiber of the present invention used in the woven or knitted fabric of the present invention preferably has a total fineness of 20 to 200 dtex, and more preferably 30 to 200 dtex. The woven or knitted fabric 1 may contain materials other than the regenerated polyester fibers of the present invention, but polyester fibers are preferred.

[0067] When the woven or knitted fabric 1 is a woven fabric, the regenerated polyester fibers of the present invention may be used for the warp and weft, and may be made into a plain weave, twill, double weave, or ripstop structure taking into consideration tear strength. Of these, plain weave is preferred. When the woven / knitted fabric 1 is a knitted fabric, it may be any of single knit (plain knit), double knit (smooth, punch, tuck reversible) and tricot, but it is preferable that the fabric has a smooth surface with little unevenness.

[0068] The woven / knitted fabric 1 preferably has a basis weight of 30 to 300 g / m2, more preferably 40 to 250 g / m2, and a cover factor of 1000 to 3000, more preferably 1300 to 2800.

[0069] The cover factor is a value calculated as follows. The cover factor (CF) is calculated by the following formula (B) for woven fabrics. In the case of objects, it is calculated using the following formula (C). JPEG2025066758000002.jpg22125JPEG2025066758000003.jpg19125

[0070] DT: Multifilament fineness (dtex) WAD: Warp density (pieces / 2.54cm) WED: Weft density (pieces / 2.54cm) CD: Course density (pieces / 2.54cm) WD: Wale density (pieces / 2.54cm) The fineness of multifilament fibers shall be measured and calculated in accordance with JIS L 1096:2010 8.9.9.1.a, Method A, for woven fabrics, and in accordance with JIS L 1096:2010 8.9.9.1.b, for knitted fabrics. The warp density and weft density shall be measured and calculated in accordance with JIS L 1096:2010 8.6.1A method, and the course density and wale density shall be measured and calculated in accordance with JIS L 1096:20 10 8.6.2.

[0071] In addition, a water repellent is preferably used in the woven or knitted fabric 1 of the present invention to impart water repellency. As the water repellent, commercially available products can be used, and examples of the water repellent include fluorine-based water repellents such as "Asahi Guard (product name)" manufactured by Asahi Glass Co., Ltd. and "NK Guard (product name)" manufactured by Nicca Chemical Co., Ltd. As the fluorine-based water repellent, in particular, a fluorine-based water repellent that does not contain perfluoroalkyl acid is preferable from the viewpoint of environmental protection. The fluorine-based water repellent is preferably used in the form of an aqueous emulsion.

[0072] In addition, from the viewpoint of environmental consideration, water repellents that do not contain fluorine (i.e., non-fluorine-based water repellents) may be used as the water repellent. Examples of non-fluorine-based water repellents include hydrocarbon-based, silicone-based, and wax-based. Commercially available products can be used as non-fluorine-based water repellents. For example, hydrocarbon-based water repellents include "Neoseed (product name)" manufactured by NICCA Chemical Co., Ltd. and "Palladium ECO (product name)" manufactured by Ohara Palladium Co., Ltd.; silicone-based water repellents include "Drypon 600E (product name)" manufactured by NICCA Chemical Co., Ltd. and "Poron (product name)" manufactured by Shin-Etsu Chemical Co., Ltd.; and wax-based water repellents include "TH-44 (product name)" manufactured by NICCA Chemical Co., Ltd. and "Neolax (product name)" manufactured by Takamatsu Oil & Fat Co., Ltd. In particular, hydrocarbon-based water repellents that are easy to increase washing durability when used in combination with other agents are preferable.

[0073] [Woven and knitted fabrics 2] The woven or knitted fabric of the present invention (hereinafter referred to as woven or knitted fabric 2) is a woven or knitted fabric containing at least a part of the mixed fiber entangled yarn of the present invention. The content of the mixed fiber entangled yarn of the present invention contained in the woven or knitted fabric 2 of the present invention is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 55% by mass or more.

[0074] The woven / knitted fabric 2 of the present invention is characterized in that the surface structure of the mixed / interlaced yarn constituting the woven / knitted fabric is specified as above, thereby improving the water repellency of the woven / knitted fabric. When the woven / knitted fabric 2 is a woven fabric, the cover factor (CF) of the woven fabric is preferably 1500 to 3000, more preferably 2200 to 2800. If the CF is less than 1500, the woven fabric will have coarse weaving points, and the number of voids in the woven fabric will increase. As a result, water droplets will tend to fall into the voids, and improvement in water repellency may not be expected. On the other hand, if the CF is more than 3000, the restraint by the weaving points will be strong, and the tear strength and burst strength of the woven fabric may decrease.

[0075] In addition, when the woven / knitted fabric 2 of the present invention is a knitted fabric, the surface density of the water-repellent woven / knitted fabric is preferably 55-150 courses / 2.54 cm and 45-100 wales / 2.54 cm, and more preferably 50-100 courses / 2.54 cm and 45-85 wales / 2.54 cm. If the course density and wale density are below the respective ranges, the knitted fabric will have coarse weaving points, and there will be a tendency for the number of voids in the knitted fabric to increase. As a result, water droplets will tend to fall into the voids, and sufficient improvement in water repellency may not be expected. On the other hand, if the course density and wale density are above the respective ranges, the constraint by the weaving points will be strengthened, and the tear strength and burst strength of the knitted fabric may decrease.

[0076] The weight of the woven or knitted fabric 2 of the present invention is 200 g / m 2 It is preferable that the thickness is less than 150 g / m 2 The lower limit of the basis weight is not particularly limited, but is, for example, 80 g / m 2 Specifically, the basis weight is preferably 80 to 200 g / m 2 , more preferably 80 to 150 g / m 2 It is.

[0077] In the woven or knitted fabric 2 of the present invention, the woven fabric is preferably a plain weave, twill weave, or satin weave, or a multi-weave structure as required. The knitted fabric is preferably a circular knitted plain weave, smooth, or warp knitted tricot, or a multi-weave structure as required. Knitted fabrics can properly maintain the unevenness of the fabric surface compared to woven fabrics, and therefore have a significantly superior water drop rolling property due to the synergistic effect with the protruding parts of the mixed fiber intertwined yarn. In order to impart water repellency to the woven or knitted fabric 2 of the present invention, it is preferable to use a water repellent. As the water repellent, a commercially available product can be used, and a fluorine-based water repellent or a non-fluorine-based water repellent as shown in the woven or knitted fabric 1 can be used.

[0078] Next, a method for producing the woven or knitted fabric 1 of the present invention will be described. [Method for manufacturing woven or knitted fabric 1] The woven or knitted fabric 1 of the present invention can be obtained by weaving and knitting the above-mentioned recycled polyester fibers to obtain a grey fabric, which is then dyed and water-repellent treated. The weaving and knitting can be performed using known weaving and knitting machines, and known equipment can be used for the preparation process prior to the weaving and knitting. In dyeing, the grey fabric is first scoured and relaxed. Scouring and relaxation can be carried out at a temperature of 80 to 130°C using a continuous or batch method. It is usually preferable to carry out the scouring and relaxation at a temperature of 100°C or less, and it is preferable to use a high-pressure liquid jet dyeing machine equipped with a jet nozzle or a spread-cloth scouring machine.

[0079] After scouring and relaxing, it is preferable to preset the woven or knitted fabric. Presetting is usually performed by dry heat treatment at 170-200°C for 30-120 seconds using a pin tenter. Presetting can prevent twisting and is effective in increasing water pressure resistance. Depending on the fabric design, presetting may be performed before scouring and relaxing. After presetting, dyeing, dehydration and drying are performed as usual.

[0080] After the dyeing process, the woven or knitted fabric is subjected to a water-repellent process. In the water-repellent process, first, an aqueous solution containing a water-repellent agent is prepared. Next, the aqueous solution is applied to the woven or knitted fabric after the above post-processing process by padding, spraying, kiss roll coating, slit coating, or the like, and then dry heat treated at 105 to 190°C for 30 to 150 seconds. The aqueous solution may also contain a crosslinking agent, a softener, an antistatic agent, or the like, as necessary. After the water-repellent process, it is preferable to calendar the woven or knitted fabric to further improve the water-repellent performance (water pressure resistance).

[0081] A method for producing the woven or knitted fabric 2 of the present invention will be described. [Method for manufacturing woven or knitted fabric 2] The woven or knitted fabric 2 of the present invention can be obtained by weaving and knitting the mixed and intertwined yarn to obtain a grey fabric, which is then dyed and water-repellent treated. The weaving and knitting can be performed using a known weaving machine and knitting machine, and the preparation process prior to the weaving and knitting can also be performed using known equipment.

[0082] In the dyeing process, the grey fabric is first scoured and relaxed. Scouring and relaxation can be carried out at a temperature of 80 to 130°C using a continuous or batch method. Usually, it is preferable to carry out the process at 100°C or less using a batch method, and it is particularly preferable to use a high-pressure liquid jet dyeing machine equipped with a jet nozzle.

[0083] After scouring and relaxing, the woven or knitted fabric may be preset. Presetting is usually done by dry heat treatment at 170-200℃ for 30-120 seconds using a pin tenter. After presetting, the fabric is dyed according to the usual method, dehydrated and dried.

[0084] After the dyeing process, the woven or knitted fabric is subjected to a water-repellent process. In the water-repellent process, first, an aqueous solution containing a water-repellent agent is prepared. Next, the aqueous solution is applied to the woven or knitted fabric after the above post-processing process by padding, spraying, kiss roll coating, slit coating, or the like, and then dry heat treated at 105 to 190°C for 30 to 150 seconds. The aqueous solution may also contain a crosslinking agent, a softener, an antistatic agent, or the like, as necessary. After the water-repellent process, the woven or knitted fabric may be calendered to further improve the water-repellent performance. EXAMPLES

[0085] The present invention will now be described in more detail with reference to the following examples, in which the various property values ​​and the like are measured and evaluated as follows: [Characteristics of recycled polyester resin] (a) Intrinsic viscosity The measurement is performed at 20°C using an equal mass mixture of phenol and tetrachloroethane as the solvent. (b) Composition of polyester resin The copolymer was dissolved in a mixed solvent of deuterated hexafluoroisopropanol and deuterated chloroform in a volume ratio of 1 / 20, and 1H-NMR was measured using a JEOL LA-400 NMR apparatus. The type and content of the copolymerized components were determined from the integrated intensity of the proton peaks of each component in the obtained chart. (c) Carboxyl end group concentration 0.1 g of the resulting recycled polyester resin was dissolved in 10 ml of benzyl alcohol, and 10 ml of chloroform was added to the solution, which was then titrated with a 1 / 10 N solution of potassium hydroxide in benzyl alcohol to determine the content. (d) Average boost speed The measurement was performed by the method described above.

[0086] [Characteristics of recycled polyester fibers] (e) Strength and elongation Measurement was performed according to JIS L 1013 using a Tensilon RTC-1210 (manufactured by Orientec Co., Ltd.). (f) Number of fuzz Using highly oriented undrawn yarn, the number of fluffs (pieces / 10 8 m) was measured. The fiber length was 3 × 10 8 I went at m. (g) Spinnability The state of yarn breakage during melt spinning to obtain highly oriented undrawn yarn was evaluated on a three-point scale as follows based on the number of yarn breakages per spindle when melt spinning was performed continuously for 24 hours. ○ The number of thread breakages was 0. △: Yarn breakage occurred 1 or 2 times. ×: Yarn breakage occurred three or more times. (h) Stretchability The state of yarn breakage during drawing of the highly oriented undrawn yarn was evaluated on a three-level scale based on the number of breaks (total number) when drawing was performed continuously for 10 hours using 100 spindles. ○ The number of cuts was 0 to 1. △: The number of cuts was 2 to 4. ×: The number of cuts was 5 or more.

[0087] [Characteristics of mixed fiber interlaced yarn] (i) Crimp rate After cutting the sample into a spool with 5 windings using a measuring machine with a frame circumference of 1.125 m, the spool was hung on a stand in a free state at room temperature for a day and a night. Next, the spool was put into boiling water with a load of 0.000147 cN / dtex applied, and subjected to a wet heat treatment for 30 minutes. After that, the spool was taken out, the moisture was lightly removed with filter paper, and the spool was left in a free state at room temperature for 30 minutes. Then, a load of 0.000147 cN / dtex and 0.00177 cN / dex (light load) were applied to the spool, and the length X was measured. Next, a load of 0.000147 cN / dtex was applied instead of the light load, and a load of 0.044 cN / dtex (heavy load) was applied instead of the light load, while the load of 0.000147 cN / dtex was still applied, and the length Y was measured. Then, the crimp rate (%) was calculated based on the formula of (YX) / Y×100. The crimp percentage was measured for five samples each, and the average of the measurements was taken as the crimp percentage for that sample. (j) Number of confounds The number of entanglements (pieces / m) of the mixed fiber entangled yarn was measured based on the JIS L1013 8.15 hook method.

[0088] [Characteristics of the fabric] (k) Water repellency (water droplet rolling angle) The water droplet rolling angle was measured by gently dropping 0.02 mL of water onto a horizontal sample (woven fabric) mounted on a horizontal plate, then gently tilting the plate, and measuring the angle at which the water droplet began to roll. (m) Texture The woven or knitted fabrics thus obtained were evaluated for feel according to the following criteria. ○: Moderate firmness, softness, and suppleness △:Normal ×: Too hard or lacking in firmness and elasticity

[0089] [Production of recycled polyester resin] Recycled polyester resin A A slurry of terephthalic acid (TPA) and ethylene glycol (EG) (TPA / EG molar ratio = 1 / 1.6) was supplied to an esterification reactor and reacted at a temperature of 250°C and a pressure of 50 hPa to obtain ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95%. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the esterification reactor, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the esterification reactor was rotating. When the internal temperature of the esterification reactor (hereinafter referred to as the "ES can") stopped decreasing, 55.0 parts by mass of recycled polyester raw material (pellet-like polyester waste generated in the process of manufacturing polyester resin) was added in a fixed amount via a rotary valve over a period of about 2 hours. At this time, the recycled polyester raw material was charged so that the molar ratio of total glycol components / total acid components (hereinafter sometimes referred to as "G / A") was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. Then, the obtained depolymerization product was pressure-fed to a polycondensation reactor (hereinafter referred to as PC can) through a candle filter with a mesh size of 20 μm set between the esterification reactor and the polycondensation reactor, and then 1.0×10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, EG slurry of titanium dioxide was added to make 0.20 mass%, and the PC can was decompressed and after 60 minutes, the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain recycled polyester resin A (intrinsic viscosity: 0.64).

[0090] Recycled polyester resin B In the same manner as in the case of recycled polyester resin A, ethylene terephthalate oligomer (number average polymerization degree: 5) with an esterification reaction rate of 95% was obtained. 30.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 70.0 parts by mass of recycled polyester raw material (same as in Example 1) was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was charged so that the G / A was 1.10. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10-4 The mixture was added so as to obtain a ratio of mol / unit, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 5 hours to obtain recycled polyester resin B (intrinsic viscosity: 0.65).

[0091] Recycled polyester resin C An ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained in the same manner as in Example 1. 45.0 parts by mass of the ethylene terephthalate oligomer was charged into an ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester raw material (PET bottles crushed or remelted and pelletized) was added at a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was charged so that the G / A was 1.16. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 mol / unit, EG slurry of titanium dioxide was added to make 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0092] Recycled polyester resin D In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 25 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make 0.05 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 280°C for 3 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.56).

[0093] Recycled polyester resin E In the same manner as in the case of recycled polyester resin A, ethylene terephthalate oligomer (number average polymerization degree: 5) with an esterification reaction rate of 95% was obtained. 30.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 2.5 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 70.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.06. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0094] Recycled polyester resin F In the same manner as in the case of recycled polyester resin A, ethylene terephthalate oligomer (number average polymerization degree: 5) with an esterification reaction rate of 95% was obtained. 50.0 parts by mass of ethylene terephthalate oligomer was charged into an ES can, and then 19.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 50.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, recycled polyester raw material (same as in Example 1) was added so that G / A was 1.36. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0095] Table 1 shows the property values ​​of the obtained recycled polyester resins A to F, and for reference, the virgin polyester resin.

[0096] [Table 1]

[0097] [Production of Regenerated Polyester Fiber (A)] Example 1 Recycled polyester resin A was spun from a spinning nozzle (hole diameter 0.15 mm, number of holes 84) equipped with a filter with a filtration grain size of 20 μm at a resin temperature of 295°C using an extruder-type melt spinning machine, and wound up at a spinning speed of 2900 m / min to obtain multifilament yarn A (highly oriented undrawn yarn) with a fineness of 45 dtex.

[0098] Example 2 Melt spinning and winding were carried out in the same manner as in Example 1, except that recycled polyester resin B was used, to obtain multifilament yarn B having a fineness of 45 dtex.

[0099] Example 3 Melt spinning and winding were carried out in the same manner as in Example 1, except that recycled polyester resin C was used, to obtain multifilament yarn C having a fineness of 45 dtex.

[0100] Example 4 Melt spinning and winding were carried out in the same manner as in Example 1, except that recycled polyester resin D was used, to obtain multifilament yarn D having a fineness of 45 dtex.

[0101] Comparative Example 1 An attempt was made to perform melt spinning in the same manner as in Example 1, except that recycled polyester resin E was used. However, the pressure rise during spinning was so rapid that many broken yarns occurred, and therefore a multifilament could not be obtained.

[0102] Comparative Example 2 Melt spinning and winding were carried out in the same manner as in Example 1, except that recycled polyester resin F was used, to obtain multifilament yarn F having a fineness of 45 dtex.

[0103] The strength, elongation, number of fluff, and runnability (yarn breakage, pressure rise) of the multifilament yarns obtained in Examples 1 to 4 and Comparative Example 2 were examined. The results are shown in Table 2.

[0104] [Table 2]

[0105] As is clear from Table 2, the multifilament yarns of Examples 1 to 4 were made of recycled polyester resins having a carboxyl end group concentration and diethylene glycol content within specific ranges, and therefore ultrafine fibers having a single fiber fineness of 0.5 decitex could be obtained with good operability (spinnability and drawability), and the multifilament yarns were excellent in both strength and elongation and free of fluff. On the other hand, in Comparative Example 1, because a recycled polyester resin with a high concentration of carboxyl end groups was used, the pressure rise during spinning was intense, and many broken yarns occurred, so a multifilament yarn could not be obtained. In Comparative Example 2, because a recycled polyester resin with a high content of diethylene glycol was used, a multifilament yarn could be obtained, but the strength was low and there was a lot of fluffing, which was problematic for practical use.

[0106] [Method for producing recycled polyester fiber (B)] [Production of multifilament yarn G] Recycled polyester resin A was spun from a spinning nozzle (hole diameter 0.3 mm, number of holes 12) equipped with a filter with a filtration grain size of 20 μm at a resin temperature of 295°C using an extruder-type melt spinning machine, and wound up at a spinning speed of 3000 m / min to obtain multifilament yarn G (highly oriented undrawn yarn) with a fineness of 40 dtex.

[0107] Example 5 [Production of mixed fiber entangled yarn] The multifilament yarn A obtained in Example 1 was prepared. Meanwhile, a multifilament yarn G (strength 2.85 cN / dtex, elongation 131%, total fineness 40 dtex, 12 filaments) was prepared. The multifilament yarns A and G were subjected to a mixed fiber entangled yarn manufacturing process as shown in Fig. 2. A disk type false twisting tool 5 was used, and the composite false twisting conditions and mixed fiber entanglement conditions were as follows, to obtain a mixed fiber entangled yarn A with an elongation of 26.6%.

[0108] <Composite false twist conditions> Surface speed of supply roller 1: 330.5 m / min Stretching ratio of polyester highly oriented undrawn yarn B: 1.235 times Surface speed of first take-off roller 2: 408.2 m / min Heater 3 temperature: (contact heater) 160℃ Twist direction: Z direction Disc structure: 1-6-1 Disc thickness: 9mm K value: 1.0 Stretching ratio during false twisting: 1.225 times Surface speed of the second take-off roller 5: 500 m / min

[0109] <Conditions for interlacing mixed fibers> Fluid nozzle 6: Interlaced nozzle Air pressure: 0.1275MPa Overfeed rate: 4.4% Surface speed of the third take-off roller 7: 478.9 m / min

[0110] [Fabric manufacturing] Next, using a water jet loom (manufactured by Tsudakoma Corp.), the mixed intertwined yarn A obtained in Example 5 was arranged in an untwisted state for both the warp and weft to weave a plain weave fabric with a warp density of 145 threads / 2.54 cm and a weft density of 115 threads / 2.54 cm. The grey fabric was scoured at 80° C. using a BOILOFF scourer (manufactured by Fukushin Kogyo Co., Ltd.). Next, a dye solution having the composition shown in the following recipe 1 was prepared, and the fabric was dyed with this dye solution for 30 minutes at 135° C. The fabric was then dried at 140° C. using a shrink surfer type dryer (manufactured by Hirano Tecseed Co., Ltd.). <Prescription 1> Dye: Disperse dye "Dianix Blue UN-SE (product name)" manufactured by Dystar Japan Co., Ltd. 2% omf Dispersant: Nikka Sunsalt SN-250E (product name) manufactured by Nicca Chemical Co., Ltd. 0.5 g / L acetic acid (98%) 0.1 mL / L Furthermore, after preparing an aqueous solution having the composition shown in the following recipe 2, the aqueous solution was applied to a woven fabric at a squeezing rate of 80% using a putter processing machine, and a dry heat treatment was performed at 120°C for 120 seconds. Then, the final setting was performed at 180°C for 30 seconds to obtain a water-repellent woven / knitted fabric (warp density 169 threads / 2.54 cm, weft density 126 threads / 2.54 cm, cover factor (CF) 2233). <Prescription 2> Fluorine-based water repellent: 50g / L "NK Guard S-07 (product name) (Rf group has 6 carbon atoms) solid content 20% by mass" manufactured by Nicca Chemical Co., Ltd. Crosslinking agent: melamine resin "Beckamin M-3 (trade name)" manufactured by DIC Corporation, 3 g / L Catalyst: "Catalyst ACX (trade name) solid content 35 mass%" manufactured by DIC Corporation, 3 g / L

[0111] Example 6 A mixed and entangled yarn B was obtained in the same manner as in Example 5, except that multifilament yarn B was used instead of multifilament yarn A in Example 5. A woven fabric was produced in the same manner as in Example 5, except that the mixed interlaced yarn B obtained was used as both the warp and weft.

[0112] Example 7 Mixed fiber entangled yarn C was obtained in the same manner as in Example 5, except that multifilament yarn H (strength 2.79 cN / dtex, elongation 133%, total fineness 40 dtex / 12 filaments) made of virgin polyester resin (polyethylene terephthalate) shown in Table 1 was used instead of multifilament yarn G. A woven fabric was produced in the same manner as in Example 5, except that the mixed interlaced yarn C obtained was used as both the warp and weft.

[0113] The property values ​​of the mixed fiber intertwined yarns and woven fabrics obtained in Examples 5 to 7 are shown in Table 3.

[0114] [Table 3]

[0115] As is clear from Table 3, the mixed fiber entangled yarns obtained in Examples 5 to 7 were made using the recycled polyester fibers obtained in Examples 1 to 3 as ultrafine fibers, so that mixed fiber entangled yarns having the desired crimp rate and entanglement number could be obtained without any problems in operability, as in the case of using ultrafine fibers made of virgin polyester resin. The woven fabrics obtained using these mixed fiber entangled yarns had excellent water repellency and a soft texture. [Explanation of symbols]

[0116] 1 First supply roller 2 Second supply roller 3. First Heater 4. False twisting tool 5 First take-off roller 6 Fluid Nozzle 7 Second take-off roller 8 Winding roller 9. Package of mixed interlaced yarn 10 Second Heater Package of YA polyester fiber (A) YB Polyester fiber (B) package

Claims

1. A polyester fiber made of a recycled polyester resin containing a component derived from at least one recycled polyester raw material consisting of a) used polyester products and b) unused polyester generated in a process for manufacturing polyester products, the recycled polyester fiber having a single fiber fineness of 0.2 to 0.9 dtex, a filament count of 40 to 320, a total fineness of 20 to 200 dtex, and a strength of 1.5 cN / dtex or more.

2. 2. The regenerated polyester fiber according to claim 1, wherein the regenerated polyester resin has a diethylene glycol content of 4 mol % or less and a carboxyl end group concentration of 30 equivalents / t or less when the total amount of all glycol components is 100 mol %.

3. A mixed fiber entangled yarn which is composed of the recycled polyester fiber according to claim 1 or 2 and a polyester fiber having a single fiber fineness of 1.0 to 5.0 dtex, and has a total fineness in the range of 40 to 300 dtex, wherein the mixed fiber entangled yarn has a false twist crimp as a whole, and a protrusion made of the recycled polyester fiber is formed on a surface portion of the mixed fiber entangled yarn.

4. The mixed fiber entangled yarn according to claim 3, wherein the polyester fiber having a single fiber fineness of 1.0 to 5.0 dtex is a polyester fiber made of a recycled polyester resin containing a component derived from at least one recycled polyester raw material of a) used polyester products and b) unused polyester generated in the process of manufacturing polyester products.

5. A woven or knitted fabric comprising the recycled polyester fiber according to claim 1 or 2.

6. A woven or knitted fabric comprising the mixed fiber interlaced yarn according to claim 3 or 4.

Citation Information

Patent Citations

  • Method for producing polyester, and polyester fiber

    JP2003160655A

  • Polyester fiber and false twist yarn comprising the same

    JP2004277919A

  • Recycled polyester resin, depolymerization product of polyester, and method for producing the recycled polyester resin

    JP2005171138A

  • Recycled polyester fiber

    JP2005206966A

  • Wet heat-resistant recycled polyester fiber

    JP2006336122A